Flood risk assessment: a review of flood damage estimation model for Malaysia - Noor Suraya, Romali; Muhammad @ S A Khushren, Sulaiman; Zulkifli, Yusop; Zulhilmi, Ismail (Penerbit Universiti Teknologi Malaysia, 2018)
Flood damage assessment is important in flood risk management for the assessment of flood vulnerability, development of flood risk map and flood management financial appraisal. In Malaysia, there is a lack of studies on flood damages estimation. In addition, the needed data for the assessment of flood damages is scarce. This review identified the approaches and problems in flood damage assessment. For Malaysia, the combination of four elements namely; flood characteristics (flood depth and flood duration), characteristic of exposed elements, value of exposed element and flood damage function curve are recommended. The scarcity of data for developing flood damage curve could partly be overcome by applying synthetic method to generate additional data from the existing flood damage data.